Measurement of macrophage phagocytic capacity by quantifying maximum membrane extension using an opsonized capillary tube assay - Dan Horonushi; Souta Suzuki; Maiha Ando; Haruka Yuki; Kenji Yasuda (Scientific Reports)
Abstract The zipper mechanism explains phagocytosis as sequential ligand–receptor interactions between macrophages and antigens, followed by the cell membrane extension for phagosome formation. Hence, the ability of macrophages to innate immunity is restricted by their capacity for engulfment related to the expansion limit of their membranes. However, the maximum expansion ability of macrophage membranes and their relationship with the phagocytosis capacity has not been rigorously investigated yet because of the lack of quantitative measurement methods of maximum cell expansion. Here, we have developed an opsonized capillary tube assay and evaluated the maximum membrane extension on the opsonized inner surface of capillary tubes from the inner round area attached to the macrophage surface. When the engulfment started, the cell membrane in the inner circle of the capillary head expanded up to 10.64 times in opsonized capillary tubes regardless of the inner diameter differences of 3 to $$7\,\upmu$$ 7 μ m. This maximum expansion ability was two times larger than those reported in the frustrated phagocytosis experiments. To support this result, we confirmed the independence of simultaneous local phagocytic responses against multiple antigens and the phagocytic ability of the outer surfaces of extending phagocytic cups. We applied this maximum expansion capacity to the opsonized microneedle phagocytosis and estimated that the required cell membrane for phagocytosis to reach the maximum expansion was up to $$5.05\,\upmu$$ 5.05 μ m area around the attached antigen. The maximum number of engulfed $$40\,\upmu$$ 40 μ m microbeads during the serial phagocytosis was 24% consume of their maximum ability of membrane extensions, suggesting that serial phagocytosis may involve another phagocytosis-number-dependent regulatory mechanism, adding to the zipper mechanism to understand the determination of phagocytosis capacity.